2021
DOI: 10.1108/jhtt-03-2021-0104
|View full text |Cite
|
Sign up to set email alerts
|

Voice assistants in hospitality: using artificial intelligence for customer service

Abstract: Purpose Voice assistants (VAs) empower human–computer interactions by recognising human speech and implementing commands pronounced by users. This paper aims to investigate VA-enabled interactions between hotels and guests in the hospitality context. The research positions VAs within the artificial intelligence (AI)-enabled Internet of Things (IoT) context, disrupting old practices and processes. Smart hospitality uses VAs to support effortless value cocreation for guests cost-effectively. The research examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 40 publications
0
53
0
2
Order By: Relevance
“…Within the scope of this research, customer satisfaction was among the most affected criteria. In addition, the technologies used in hotels help to improve customer service, expand operational capacity and create cost advantages (Buhalis & Moldavska, 2021). As in all sectors, providing cost advantage is the priority duties of hotel managers.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Within the scope of this research, customer satisfaction was among the most affected criteria. In addition, the technologies used in hotels help to improve customer service, expand operational capacity and create cost advantages (Buhalis & Moldavska, 2021). As in all sectors, providing cost advantage is the priority duties of hotel managers.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…However, customers do not always perceive smart technologies positively. With hospitality perceived as high-touch, many are resistant to self-service technologies, Smart hospitality claiming they lessen the service encounter (Stamolampros et al, 2019;Choi et al, 2020;Chen et al, 2021;Buhalis and Moldavska, 2022). Robotics can be used to create novel experiences (Pizam et al, 2022;Tung and Au, 2018) and have been shown to positively affect service quality and travellers' intention to revisit (Çakar and Aykol, 2021).…”
Section: Hotel Guestsmentioning
confidence: 99%
“…Often data remain in analogue form or in silos within departmental applications, preventing its diffusion and use. Overall, many hotel properties lack the technological infrastructure needed to exploit Smart Hospitality effectively (Buhalis and Moldavska, 2022). Even though smart hospitality is broader than just technology alone, without this key enabler it is impossible to profit from such developments.…”
Section: Smart Hospitality Stakeholders: Reengineering Value Chains A...mentioning
confidence: 99%
“…Robots, Artificial Intelligence and Service Automation (RAISA) technologies are increasingly evident in tourism (Ivanov and Webster, 2019). Customer service Bots, such as ZOE of MSC Cruises (Buhalis and Moldavska, 2021) and robots like "Pepper" of Costa Cruises, provide concierge services about on-board facilities and shore trips whilst collecting evaluations about the experience. They are available 24/7 to address passenger needs, give information and can customise experiences based on individual preferences, using streaming analytics, contextual awareness and machine learning.…”
Section: Smart Technology Applicationsmentioning
confidence: 99%